Miscellaneous notes on Begonia medogensis (Begoniaceae) - Chen, Wen-Hong; Tian, Dai-Ke; Radbouchoom, Sirilak; Xiao, Yan; Cong, Yi-Yan; Guo, Shi-Wei; Shui, Yu-Min (Phytotaxa, 2018)
During the review progress of a manuscript describing a new species from Xizang (Tibet), we found that, close to acceptance of our manuscript, the same species had just been published as Begonia medogensis. For better understanding this species, we supplemented the description of this species with further illustrations, additional specimens, updated distribution map, further comparison with similar species and a conservation assessment (NT).